Benefits of vocational education and Training in Europe for people, organisations and countries - (:unkn) unknown (Publications Office of the European Union, 2013)
"People, organisations and governments invest in vocational education and training (VET) because of its positive outcomes, such as higher wages, improved productivity and economic growth. But VET also brings non-economic benefits, such as lower absenteeism and less crime. Research on VET's benefits has focused on specific relationships, such its impact on productivity or health. Insufficient attention has been given how VET’s benefits interact in organisations. VET contributes directly to higher productivity by increasing skill levels, but also indirectly by increasing job satisfaction and lowering absenteeism." This publication summarises Cedefop's work on VET's benefits since 2008. It focuses on VET, thus contrasting, where possible, its specific outcomes with those from general education. It also looks at how VET generates its perceived benefits. The publications shows that VET not only has economic benefits (wages for individuals, improved productivity for organisations, more economic growth for countries), but also many further benefits that are difficult to express in monetary terms (e.g. better health and satisfaction with life and leisure, quality of participation in public life). "Finally, this publication examines how VET's market and non-market benefits interact in organisations and how they can be maximised to improve producativity. It shows that to achieve competitive advantage, an organisation's VET policies and its wider human resource management practices must be consistent with how it competes in its markets." (Editor, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; G 1.3.3.1 Qualifikationsverwertung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 4.3.6 Human Capital; I 2.2 Europa; Berufsausbildung; Berufliche Weiterbildung; Qualifikationsverwertung; Ökonomische Faktoren; Bildungsertrag; Sozialkapital; Humankapital; Indikatoren; Europa